Access, socioeconomic environment, and death from COVID-19 in Nebraska - Bai, He; Schwedhelm, Michelle; Lowe, John-Martin; Lookadoo, Rachel E.; Anderson, Daniel R.; Lowe, Abigail E.; Lawler, James V.; Broadhurst, M. Jana; Brett-Major, David M. (Frontiers in Public Health, 2022)
Our study assesses whether factors related to healthcare access in the first year of the pandemic affect mortality and length of stay (LOS). Our cohort study examined hospitalized patients at Nebraska Medicine between March and October 2020 who were tested for SARS-CoV-2 and had a charted sepsis related diagnostic code. Multivariate logistic was used to analyze the odds of mortality and linear regression was used to calculate the parameter estimates of LOS associated with COVID-19 status, age, gender, race/ethnicity, median household income, admission month, and residential distance from definitive care. Among 475 admissions, the odds of mortality is greater among those with older age (OR: 1.04, 95% CI: 1.02 to 1.30) and residence in an area with low median household income (OR:1.83, 95%CI: 0.48 to 6.98). Those with non-COVID-19 sepsis had longer LOS (Parameter Estimate: -5.11, adjusted 95% CI: -7.92 to -2.30). Distance from definitive care had trends towards worse outcomes (Parameter Estimate: 0.164, adjusted 95% CI: -1.39 to 1.97). Physical and social aspects of access to care are linked to poorer COVID-19 outcomes. Non-COVID-19 healthcare outcomes may be negatively impacted in the pandemic. Strategies to advance patient-centered outcomes in vulnerable populations should account for varied aspects (socioeconomic, residential setting, rural populations, racial, and ethnic factors). Indirect impacts of the pandemic on non-COVID-19 health outcomes require further study.